2020
DOI: 10.1007/s10658-020-02158-8
|View full text |Cite
|
Sign up to set email alerts
|

Disease responses of hexaploid spring wheat (Triticum aestivum) culms exhibiting premature senescence (dead heads) associated with Fusarium pseudograminearum crown rot

Abstract: Hexaploid spring wheat (Triticum aestivum) may exhibit significant crown rot disease responses to infection by Fusarium pseudograminearum, with a range of susceptibility levels available in commercial cultivars. Dry conditions during grain-fill may lead to the expression of prematurely senescing culms, which typically fail to set grain. Assessment of hexaploid spring wheat plants exhibiting both non-senescent and prematurely senescent culms was performed using visual discolouration, Fusarium pseudograminearum … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 36 publications
2
14
1
Order By: Relevance
“…2). This result is consistent with the widely reported lack of resistance that durum wheat exhibits to crown rot, when compared with bread wheat (Hollaway et al 2013;Knight and Sutherland 2015;Knight et al 2017;Martin et al 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2). This result is consistent with the widely reported lack of resistance that durum wheat exhibits to crown rot, when compared with bread wheat (Hollaway et al 2013;Knight and Sutherland 2015;Knight et al 2017;Martin et al 2013).…”
Section: Discussionsupporting
confidence: 92%
“…These prematurely senesced spikes contain either no grain or shriveled grain, depending on the timing of stress relative to grain development. A recent study has demonstrated that tillers displaying greater severity of stem browning and F. pseudograminearum biomass more typically exhibit whiteheads (Knight et al 2017).…”
mentioning
confidence: 99%
“…Crown rot is a significant stubble-soil fungal disease that affects the cereal industry worldwide as it has been reported in the U.S., China's southeast coast region, Africa, central Europe, and Australasia [1][2][3][4]. Fusarium pseudograminearum is the major contributing pathogen causing crown rot that is commonly found in Australian wheat [5]. Although wheat can be influenced by other fungal diseases, F. pseudograminearum has been identified and detected in 48% of fungal disease isolates from wheat in Australia [1].…”
Section: Introductionmentioning
confidence: 99%
“…For example, if wheat, at the milk stage, experiences reduced rainfall, the probability of whitehead appearance in the disease-infected wheat crops will greatly increase [21,22]. The pathogen colonizes and damages the plants' vascular system, which is responsible for water and nutrient uptakes in the plant [5], and water stress during or shortly after the wheat flowering period will increase the symptoms of the disease [23]. Once wheat is infected with crown rot, the accumulation of a high level of the mycotoxin deoxynivalenol (DON) will make the grains inedible [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Saprotrophic growth of fungal pathogens is likley to depend on moisture, stubble characteristics and the individual different species requirements, plus additional factors like temperature and competition between microbes (Pfender et al 1988). In susceptible crops, significant mycelial growth may have already occurred prior to senescence (Knight et al 2021Petronaitis et al 2020), so the infection status of a crop at maturity should also be considered. Linking the pathogenic (in-crop) colonisation with saprotrophic (postharvest) colonisation of cereal stubble is therefore needed under field conditions to fully illustrate the effect of host susceptibility on pathogen inoculum dynamics within and between seasons.…”
mentioning
confidence: 99%